2021
DOI: 10.1002/hpm.3399
|View full text |Cite
|
Sign up to set email alerts
|

Medical disputes and patient satisfaction in China: How does hospital management matter?

Abstract: Objective Satisfaction with healthcare may be captured by surveys of patients and staff, or in extreme cases, the number and severity of medical disputes. This study tries to investigate the relationship between satisfaction and hospital management as well as the role of good management in preventing medical disputes ex ante. Method We investigate this relationship using information on management practices collected from 510 hospitals in mainland China using the World Management Survey questionnaire and combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…(10) The results of this study revealed that patient's satisfaction was higher in respondents with low education level and difference in satisfaction level of the respondents with variable educational backgrounds was statistically significant (0.008) which is consistent with the results Wang M et al in which mean percent satisfaction score was higher in patients having intermediate and above as compared to the patients, having under matric category of education and lowest satisfaction level. (11) In our study the monthly family income was highly associated with patient satisfaction with the outpatient department services that was consistent with other studies conducted in Pakistan. (2) The health system of Pakistan should be devised in such a way which escalate client satisfaction with health care organizations by formulating policies through which customer friendly services can be provided.…”
Section: Discussionsupporting
confidence: 92%
“…(10) The results of this study revealed that patient's satisfaction was higher in respondents with low education level and difference in satisfaction level of the respondents with variable educational backgrounds was statistically significant (0.008) which is consistent with the results Wang M et al in which mean percent satisfaction score was higher in patients having intermediate and above as compared to the patients, having under matric category of education and lowest satisfaction level. (11) In our study the monthly family income was highly associated with patient satisfaction with the outpatient department services that was consistent with other studies conducted in Pakistan. (2) The health system of Pakistan should be devised in such a way which escalate client satisfaction with health care organizations by formulating policies through which customer friendly services can be provided.…”
Section: Discussionsupporting
confidence: 92%
“…With systematic interventions recognized as an important approach to reduce medical errors 34 , the strong association between the cluster outcome and number of medical disputes indicate that targeted interventions can be carried out within specific clusters to reduce the number of medical disputes. Earlier studies demonstrate that hospital management can play a role in dispute prevention 35 ; our study shows that hospital taxonomy can be used to provide a policy framework and contribute to dispute prevention from healthcare system level.…”
Section: Discussionmentioning
confidence: 72%
“…Hospital management is closely related to clinical performance and patient satisfaction [ 1 , 2 ]. As the country faces fast-growing demand and health care expenditures, the establishment of a modern hospital management system to improve the hospital management practices and operational efficiency of Chinese hospitals has been a policy target at the national level [3] .…”
Section: Methods Overviewmentioning
confidence: 99%